Microsoft SharePoint 2010 administrator's companion - English, Bill, 1961-; Microsoft SharePoint Teams (Redmond, Wash. : Microsoft ; Farnham : O'Reilly [distributor], 2011)
A guide to SharePoint 2010 administration covers such topics as architecture, deployment scenarios, design, security, Web content management, and business intelligence.
Keywords: Microsoft SharePoint (Electronic resource); Microsoft SharePoint (Electronic resource); Intranets (Computer networks); Intranets; Web servers